Analisis Gaya Kepemimpinan Kepala Sekolah Dalam Mengembangkan Mutu Sekolah Dasar - Besse Herlina; Darwis Darwis; Besse Sulfiani (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to analyze the principal’s leadership style in developing school quality at SD Negeri 213, Lapongkoda, Wajo Regency, South Sulawesi. This study uses a qualitative approach. The location of this research is SD Negeri 213, Lapongkoda, Wajo Regency, South Sulawesi Province. Data collection techniques through interviews, observation and documentation. Data analysis used descriptive analysis. The results of this study indicate that first, the principal’s leadership style in quality development at SD Negeri 213, Lapongkoda, Wajo, South Sulawesi is a delegation leadership style, this can be seen from the principal's leadership which has been carried out by persuasion; create harmonious cooperation and participation of subordinates; foster loyalty and motivate subordinates, and involve subordinates in making a decision; and second, supporting factors for the principal’s leadership in developing the quality of SD Negeri 213, Lapongkoda, Wajo Regency, South Sulawesi Province, among others: building a synergistic relationship with the local government in this case starting from the sub-district head, police chief, Koramil, in creating security and order school environment; and the inhibiting factors include: decision making on a policy is slow, because school principals rarely meet directly with teachers during the pandemic.